Display of receptor-binding domain of SARS-CoV-2 Spike protein variants on the Saccharomyces cerevisiae cell surface - Xing, Hongguan; Zhu, Liyan; Wang, Pingping; Zhao, Guoping; Zhou, Zhihua; Yang, Yi; Zou, Hong; Yan, Xing (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19), represents a significant global human health threat. The most effective way to end the pandemic is timely vaccination. In this study, the receptor-binding domains (RBDs) of Spike protein of the initial strain of SARS-CoV-2 and its variants, B.1.1.7 (Alpha), B.1.351 (Beta), and B.1.617.1 (Kappa), were successfully displayed on the surface of a Saccharomyces cerevisiae strain for development as a vaccine candidate. To rapidly express the recombinant protein and avoid the need for expensive galactose as an inducer, the gal80 gene of S. cerevisiae was knocked out, and the conventional 72 h culture period was thus successfully shortened to 24 h. Mice vaccinated against variant B.1.617.1 showed robust humoral and cellular immune responses. Moreover, the antiserum in the B.1.671.1 group had neutralizing activity against wild-type RBD and high binding titers against RBD mutants of variants B.1.351 and B.1.1.7. Double deglycosylation at N331Q and N343Q resulted in marked reduction of the affinity of RBD binding to angiotensin converting enzyme 2 (ACE2) and escaped antibody neutralization. This study demonstrates that yeast surface display technology can provide an alternative approach to rapid large-scale preparation of promising SARS-CoV-2 vaccine candidates at low cost.